EFFECT OF SPECIFIC TRAINING ON SELECTED BIOMOTOR VARIABLES OF DEXTEROUS - Sunil Kumar; Dr.Ajaz Ahmad Dar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Dexterous refers to the skill and grace in physical movement, especially in the use of the hands, an individual who is more dexterous with the right hand is called right-handed (dextralists), and one who is more skilled with the left is said to be left-handed (sinistralists). The purpose of the study was to find out the effect of specific training on selected biomotor variables such as strength and coordination of dexterous. To achieve the purpose 40 right hand dominance college men students from Annantnag district, Jammu & Kashmir, India were selected as subjects at random and their age ranged between 18-21 years, the selected subjects were divided in to two groups namely physical training (n=20) and control (n=20). The physical training group underwent training for 60 min/4 days/15 weeks. The maximum strength (handgrip dynamometer) and hand screwing coordination (Bennit hand tool dexterity test), were selected as dependent variables and tested before and after the experimental period for both the groups. The collected data were analyzed by using ANCOVA. Further, independent‘t’ was calculated to find out the difference between left and right hand and the magnitude of Improvement was also calculated to find out the level of improvement on dexterous. Level of confidence was fixed at 0.05. The result of the study shows that the physical training improved the maximum strength and coordination compared to control group. The difference between right and left hand on maximum strength and coordination is insignificant. Hence, it was concluded that physical training may be given to improve the dexterous (use of hands) level and quality.